A mechanistic framework for noncell autonomous stem cell induction in Arabidopsis - Daum, Gabor; Medzihradszky, Anna; Suzaki, Takuya; Lohmann, Jan U. (Proceedings of the National Academy of Sciences of the United States of America, 2014)
Cell-cell communication is essential for multicellular development and, consequently, evolution has brought about an array of distinct mechanisms serving this purpose. Consistently, induction and maintenance of stem cell fate by noncell autonomous signals is a feature shared by many organisms and may depend on secreted factors, direct cell-cell contact, matrix interactions, or a combination of these mechanisms. Although many basic cellular processes are well conserved between animals and plants, cell-to-cell signaling is one function where substantial diversity has arisen between the two kingdoms of life. One of the most striking differences is the presence of cytoplasmic bridges, called plasmodesmata, which facilitate the exchange of molecules between neighboring plant cells and provide a unique route for cell-cell communication in the plant lineage. Here, we provide evidence that the stem cell inducing transcription factor WUSCHEL (WUS), expressed in the niche, moves to the stem cells via plasmodesmata in a highly regulated fashion and that this movement is required for WUS function and, thus, stem cell activity in Arabidopsis thaliana. We show that cell context-independent mobility is encoded in the WUS protein sequence and mediated by multiple domains. Finally, we demonstrate that parts of the protein that restrict movement are required for WUS homodimerization, suggesting that formation of WUS dimers might contribute to the regulation of apical stem cell activity.
Gesehen am 14.07.2020